1989
DOI: 10.1254/jjp.49.181
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for possible analgesic mechanism of electroacupuncture: Effects on neuropeptides and serotonergic neurons in rat spinal cord.

Abstract: Abstract-The possible mechanism of electroacupuncture (EAc) in reference to the effects of neuropeptides on serotonergic neurons in rat spinal cord was studied. The tested drugs were administered by intrathecal injection or spinal push-pull perfusion.The results showed that baclofen, substance P (SP) and naloxone administered intrathecally could reduce the tail pressure pain threshold. The pain threshold was increased by met-enkephalin (EK) and EAc. The action of EAc was antagonized by naloxone. The release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…This fact shows that analgesia provided by irradiation of AcP by low-intensity microwaves under conditions of visceral pain is mediated (at least, to a considerable extent) by the activity of the cerebral serotonergic system. These results agree with the published data on analgesia induced by electropuncture; in this case, the analgesia state is accompanied by intensification of the release of serotonin [26]. It is obvious that the latter amine is one of the most important compounds that mediate analgesia induced by both acupuncture and electropuncture [27,28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This fact shows that analgesia provided by irradiation of AcP by low-intensity microwaves under conditions of visceral pain is mediated (at least, to a considerable extent) by the activity of the cerebral serotonergic system. These results agree with the published data on analgesia induced by electropuncture; in this case, the analgesia state is accompanied by intensification of the release of serotonin [26]. It is obvious that the latter amine is one of the most important compounds that mediate analgesia induced by both acupuncture and electropuncture [27,28].…”
Section: Discussionsupporting
confidence: 91%
“…Both acupuncture and electropuncture result in activation of structures of the serotonergic system [8,9] (especially of neuronal systems of the nucl. raphe magnus [10]) and in increased release of serotonin [11]. A decrease in the level of serotonin in the brain after blocking of synthesis of this amine decreased the level of analgesia induced by acupuncture [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The non-endorphinergic actions may be mediated by monoaminergic neurons [5,30,32]. Evidence from animal experiments implies that EAc is capable of influencing the synthesis and release of serotonin (5-HT) and norepinephrine (NE) in the central nervous system (CNS).…”
mentioning
confidence: 99%
“…[51][52][53][54] One study showed that acupuncture-induced analgesia is created by both central and peripheral mechanisms; the peripheral endorphin release plays a role in downregulating the neurogenic inflammation. 55 Central mechanisms include initiating descending pain control through the insular and frontal cortex activation of the periaqueductal gray, the strongest center to suppress pain, via the spinoreticulothalamic tract.…”
Section: Discussionmentioning
confidence: 99%